2007
DOI: 10.1016/j.jasms.2007.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Fragmentation of ions in a low pressure linear ion trap

Abstract: The efficiency of in-trap fragmentation in a low-pressure linear ion trap (LIT), using dipolar excitation, is dependent upon the choice of both the excitation q and the drive frequency of the quadrupole. In the work presented here, fragmentation efficiencies have been measured as a function of excitation q for drive frequencies of 816 kHz and 1.228 MHz. The experiments were carried out by fragmenting reserpine (609.23¡448.20 Th and 397.21¡365.19 Th transitions) and caffeine (195¡138 Th and 138¡110 Th transitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
16
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…Second, the effective potential well depth is greater in the x direction than in the y direction. Collings [17] has shown that at q Ϸ 0.2, small increases in well depth can give relatively large increases in fragmentation efficiency (at least at ca. 3 ϫ 10 Ϫ5 Torr).…”
Section: Resultsmentioning
confidence: 99%
“…Second, the effective potential well depth is greater in the x direction than in the y direction. Collings [17] has shown that at q Ϸ 0.2, small increases in well depth can give relatively large increases in fragmentation efficiency (at least at ca. 3 ϫ 10 Ϫ5 Torr).…”
Section: Resultsmentioning
confidence: 99%
“…Early MRM 3 studies with quadrupole linear ion trap (Q/LIT) instruments focused on characterization and identification in proteomics (8,9 ) and genomics (10 ). Newer-generation Q/LIT instruments have demonstrated greater quantitative sensitivity along with reduced cycle times owing to decreased excitation times for MRM 3 experiments (11,12 ). These technological advances have made MRM 3 detection more compatible with both the fast liquid chromatography used by modern LC-MS platforms and the sensitivity requirements of quantitative clinical analysis.…”
mentioning
confidence: 99%
“…T he in-trap fragmentation of ions in a low-pressure (Ͻ5e-5 Torr) linear ion trap (LIT), such as the 4000 QTRAP hybrid linear ion trap triple quadrupole mass spectrometer, require excitation periods typically ranging from 50 to 200 ms. This is due to the low collision rates between the ion and the background nitrogen which are typically about a few collisions every millisecond [1]. Low-pressure LITs rely on the presence of higher order fields to keep ions confined during the excitation process and, as a result, it is necessary to use excitation amplitudes ranging from 10 to 100 mV to reduce the degree of ion ejection.…”
mentioning
confidence: 99%
“…This is due to the low collision rates between the ion and the background nitrogen which are typically about a few collisions every millisecond [1]. Low-pressure LITs rely on the presence of higher order fields to keep ions confined during the excitation process and, as a result, it is necessary to use excitation amplitudes ranging from 10 to 100 mV to reduce the degree of ion ejection.…”
mentioning
confidence: 99%
See 1 more Smart Citation